1995
DOI: 10.1083/jcb.129.3.619
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid-anchored proteins in neuroblastoma cells form detergent-resistant complexes without caveolin.

Abstract: Abstract. It has been known for a number of years that glycosyl-phosphatidylinositol (GPI)-anchored proteins, in contrast to many transmembrane proteins, are insoluble at 4°C in nonionic detergents such as Triton X-100. Recently, it has been proposed that this behavior reflects the incorporation of GPI-linked proteins into large aggregates that are rich in sphingolipids and cholesterol, as well as in cytoplasmic signaling molecules such as heterotrimeric G proteins and src-family tyrosine kinases. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
235
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(255 citation statements)
references
References 53 publications
16
235
0
4
Order By: Relevance
“…Caveolaedependent endocytosis also requires intact lipid rafts and hence, is normally inhibited by cholesterol depletion (Murata et al, 1995). Caveolin is a key component of caveolae (Morrow & Parton, 2005); however, a number of previous studies have shown that RAW264.7 cells lack caveolin (Cameron et al, 1997;Fra et al, 1994;Gorodinsky & Harris, 1995;Lyden et al, 2002) and we have confirmed these observations in our RAW264.7 cells. These data do not rule out the possibility that MNV-1 infection may occur through a caveolae-dependent pathway in other cell types that express caveolin.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Caveolaedependent endocytosis also requires intact lipid rafts and hence, is normally inhibited by cholesterol depletion (Murata et al, 1995). Caveolin is a key component of caveolae (Morrow & Parton, 2005); however, a number of previous studies have shown that RAW264.7 cells lack caveolin (Cameron et al, 1997;Fra et al, 1994;Gorodinsky & Harris, 1995;Lyden et al, 2002) and we have confirmed these observations in our RAW264.7 cells. These data do not rule out the possibility that MNV-1 infection may occur through a caveolae-dependent pathway in other cell types that express caveolin.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, we investigated the role of caveolae in MNV-1 infection. Caveolae formation requires caveolin (Morrow & Parton, 2005); however, a number of reports have shown that RAW264.7 cells lack caveolin and therefore caveolae (Cameron et al, 1997;Fra et al, 1994;Gorodinsky & Harris, 1995;Lyden et al, 2002). In order to confirm the absence of caveolin-1 in our RAW264.7 cells, we subjected RAW264.7 cell lysates to immunoblotting.…”
mentioning
confidence: 99%
“…15 and as described below), and both contain similar amounts of cellular protein (Ͻ2% of the total). 2 By these criteria, the domains obtained using 0.05% Triton X-100 for cell lysis appear to be identical to other membrane domains previously described that do not contain caveolin (10,(13)(14)(15). Furthermore, the aggregation-dependent association of Fc⑀RI with membrane domains shows selectivity among transmembrane cell surface receptors, as Fc⑀RI but not Type I interleukin-1 receptors, both expressed on Chinese hamster ovary cells, associate with membrane domains following aggregation.…”
Section: Resultsmentioning
confidence: 67%
“…In this instance APP was shown to interact directly with caveolin, and depletion of the latter protein using antisense oligonucleotides prevented α-secretase cleavage, suggesting that caveolin may have a role in the α-secretase-mediated processing of APP in non-neuronal cells. However, we have detected only a very small proportion of APP in DIGs isolated from COS-7 cells using the same methodology (E. T. Parkin, A. J. Turner and N. M. Hooper, unpublished work), and, as caveolin is absent from neuronal cells [16,27,28], the relevance of this observation to the processing of APP in the brain remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…Whilst caveolin is highly expressed in lung and muscle, it is undetectable in other tissues such as spleen, kidney, liver, brain and testis [16]. Despite the absence of caveolin, DIGs can be isolated from neuronal sources and are found to contain a number of GPI-anchored proteins, such as alkaline phosphatase, 5h-nucleotidase, F3 protein, the prion protein [24][25][26][27], tyrosine kinases, and α-and β-subunits of heterotrimeric G-proteins [28,29]. Another protein, flotillin, has been found to be present exclusively in DIGs isolated from neuronal sources and can, therefore, be used in place of caveolin as a transmembrane polypeptide-anchored marker for these membrane domains [30][31][32].…”
Section: Introductionmentioning
confidence: 99%